Distribution of Vibrio alginolyticus-like species in Shenzhen coastal waters, China - Chen,Ming-Xia (2011)
We investigated the distribution of vibrios in Shenzhen coastal waters in order to obtain valuable information for the aquaculture industry and a health warning system. Quantities of vibrios from surface waters ranged from 0 to 4.40×10(4) CFUs mL-1 in April (spring), while from 0 to 2.57×10³ CFUs mL-1 in September (autumn); the abundance of V. alginolyticus-like species from surface water ranged from 0 to 6.72×10³ CFUs mL-1 in April (spring) and from 0 to 1.28×10³ CFUs mL-1 in September (autumn); higher counts were observed in spring. The V. alginolyticus-like species was dominant in Shenzhen coastal waters, with the highest abundance in the clean region (stations YMK001 and GDN064) in April, suggesting that Vibrio spp. were naturally occurring bacteria in marine environments. The correlation between the abundance of vibrios (including V. alginolyticus-like species) and environmental factors varied in different regions and different seasons. There were no vibrios detected when the salinity was less than 11.15 in the Zhujiang River estuary, which indicated that salinity played a key role in the distribution of vibrios and V. alginolyticus-like species.